2012
DOI: 10.1177/145749691210100310
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Has a Negative Impact on Clinical Outcome after Total Knee Arthroplasty

Abstract: Background and Aims: Obesity has been linked to the development of osteoarthritis of the knee and since the incidence of obesity is increasing, the need for total knee arthroplasty (tka) is likely to increase. conflicting findings have been reported concerning the relationship between obesity and tka. it has been shown in several studies, that obese patients have poorer clinical results after operation. On the other hand it has also been reported similar results for obese and non-obese patients. the purpose of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
27
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 23 publications
(20 reference statements)
4
27
0
1
Order By: Relevance
“…[6][7][8] Furthermore previous papers have acknowledged that people who are obese have a poorer clinical outcome after hip or knee replacement. 9,10 To address these differences in outcomes and perceived post-operative complications, some arthroplasty candidates have undergone bariatric surgery procedures prior to their total hip (THR) or total knee replacement (TKR). 11 Such procedures have included gastric bypass, sleeve gastrectomy, stomach partition using staples and gastric balloon insertion.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Furthermore previous papers have acknowledged that people who are obese have a poorer clinical outcome after hip or knee replacement. 9,10 To address these differences in outcomes and perceived post-operative complications, some arthroplasty candidates have undergone bariatric surgery procedures prior to their total hip (THR) or total knee replacement (TKR). 11 Such procedures have included gastric bypass, sleeve gastrectomy, stomach partition using staples and gastric balloon insertion.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10]15,[19][20][21]23,24 While there is a broad consensus that obesity is directly associated with these complications, based on individual studies, it is unclear whether specific BMI cutoffs exist above which patients are placed at a significantly higher risk of developing perioperative complications. 9,15,20 A recent study by Gillespie and Porteous 9 reiterated this point when the authors were not able to identify a significant BMI cutoff to differentiate between high risk and low risk patients.…”
mentioning
confidence: 99%
“…A recent meta-analysis by Kerkhoffs et al32 that included over 15,000 TKA patients concluded that obesity is associated with higher rates of infection (OR = 1.9), deep infection (OR = 2.4), and revision surgery (OR = 1.3). Obese patients also have significantly higher postsurgical WOMAC scores versus the nonobese 33. Additionally, age and gender are known influencers of acute postoperative pain, clinical outcomes, functional limitations, length of hospital stay, and mortality following knee arthroplasty 34–36.…”
Section: Discussionmentioning
confidence: 99%